Wzorzec osobowy czy wzorzec postępowania? Przyczynek do nowej definicji formułowanej z punktu widzenia historyka na przykładzie szlachty polskiej przełomu średniowiecza i czasów nowożytnych - Urszula Świderska-Włodarczyk (In Gremium. Studies in History, Culture and Politics, 2015)
Role model or model of decorum? A contribution to a new definition formulated from the point of view of a historian on the example of the Polish gentry at the turn of the Middle Ages and Modern TimesIn the context of historical research, the concept of role model is incongruent. For this reason, it should give way to the term model of decorum. Such a choice enforces the division of models of decorum into personal (formulated in relation to real persons) and impersonal (allegoric ones, concerning registers, sets, or lists of depersonalized traits ascribed to roles played and positions held). In such an understanding, every model of decorum is a real, available, and realized phenomenon, and simultaneously a mental fact embedded in the awareness of all times. As such it is a result of group and individual expectations. The expectations consist of four basic components: genealogical determinant (determined by birth); personalitydeterminant (visible in personal virtues); occupational determinant (determining professionalism in performing held offices and positions); and socio-religious determinant (allowing positive existence in the frameworks established by the state, Church, class, as well as micro-community, i.e. neighbors, friends, and family. The very concept of model of decorum is both a stable and a changeable value. Its stability is determined by an indisputable co-existence of particular components, while its changeabilityby relativism and relevance of formulated judgements as well as shifts in gravity, dictated by historical processes. The negative of a model is its anti-model, and as such it fits within the same structural framework, with the exception that due to its bipolar distinctness it is the negation of a model and its anti-model. Every model of decorum (personal or impersonal) was located in the sphere of desirable and available aspirations whose realization guaranteed social order and national well-being.